UV-assisted synthesis of long-wavelength Si-pyronine fluorescent dyes for real-time and dynamic imaging of glutathione fluctuation in living cells. Issue 28 (24th June 2016) - Nie, Hailiang; Qiao, Liang; Yang, Wen; Guo, Bingpeng; Xin, Fangyun; Jing, Jing; Zhang, Xiaoling
Abstract : Long-wavelength Si-pyronine fluorescent dyes are synthesized for reversible, real-time and dynamic imaging of glutathione fluctuation in living cells. Abstract : Changes in intracellular glutathione (GSH) concentration are closely linked with various cellular physiological and pathological mechanisms. In the present work, four long-wavelength Si-pyronine (SiP) fluorescent dyes are readily synthesized via a UV-assisted aromatization reaction, and used for real-time, dynamic and reversible monitoring of GSH changes in vitro and in living cells. Based on the mechanism that Si atom incorporation greatly increases the pyronine affinity towards sulfhydryl (–SH), SiPs can undergo ultrafast and reversible Michael addition with biological thiols, leading to fluctuations in fluorescence intensity due to the interruption and restoration of their π-conjugation. Relying on the unique reactivity of SiPs with GSH under physiological conditions, the fluorescence intensity of SiPs responds to GSH changes with high sensitivity. SiPs also exhibit excellent photophysical properties including deep-red to near-infrared excitation wavelength (>600 nm), a high fluorescence efficiency (0.20–0.41) in aqueous media, suitable water-solubility and membrane permeability. Using SiP-Pr to incubate with HeLa cells, we achieved real-time, dynamic and repeated imaging of fluctuations in intracellular GSH homeostasis under N -ethylmaleimide stimulation.